Inducible Left Ventricular Outflow Tract Obstruction in Patients Undergoing Liver Transplantation: Prevalence, Predictors, and Association With Cardiovascular Events. Issue 2 (February 2021) - Cailes, Benjamin; Koshy, Anoop N.; Gow, Paul; Weinberg, Laurence; Srivastava, Piyush; Testro, Adam; Peverelle, Matthew; Ko, Jefferson; Salehi, Hamid; Jones, Elizabeth F.; Calafiore, Paul; Farouque, Omar
Abstract : Background: Inducible left ventricular outflow tract obstruction (LVOTO) is often encountered in liver transplantation (LT) candidates during cardiac workup. While the impact of LVOTO on adverse cardiovascular hemodynamics is well reported, it is unclear whether it predisposes to perioperative cardiovascular complications. Methods: Consecutive patients with end-stage liver disease undergoing dobutamine stress echocardiography (DSE) were evaluated at an LT center between 2010 and 2017. Perioperative major adverse cardiovascular events (MACEs) at 30 days and all-cause death were recorded from a prospectively maintained LT database. Results: We evaluated 560 patients who underwent DSE during LT workup, with LVOTO identified in 24.3% (n = 136). Of these, 309 patients progressed to transplant. Patients with LVOTO demonstrated a lower peak systolic blood pressure (SBP) and an overall reduction in SBP on DSE. A total of 85 MACEs were recorded in 72 patients (23.3%) including 3 deaths, 19 cases of heart failure, 11 cardiac arrests, 8 acute coronary syndromes, and 44 arrhythmias. MACE occurred in 15/64 patients (23.4%) with LVOTO and 57/245 (23.3%) without ( P = 0.92). There was an increased risk of perioperative cardiac arrest in patients with LVOTO (7.4% versus 2.4%, P = 0.04). Intraoperatively, patients with LVOTO required higher doses of vasopressors ( P = 0.01) and received greater volumes of fluid (10.5 ± 8.1 versus 8.4 ± 6.4 L, P = 0.03). Conclusions: Patients with end-stage liver disease and LVOTO demonstrate a reduction in SBP during physiological stress that may translate to hemodynamic instability during LT. LVOTO was not associated with an increased rate of perioperative MACE or death.